The Influence Of Leverage And Firm Size On Profitability At PT Adhi Karya (Persero) TBK For The Period 2014-2023 - Sanjaya, Rudi; Ananda, Zahra Oktavia (Jurnal Fokus Manajemen, 2025)
This research investigates the influence of Leverage and Firm Size on the Profitability of PT Adhi Karya (Persero) Tbk during the 2014–2023 period, both individually and jointly. The financial indicators examined include the Debt to Equity Ratio (DER), Firm Size, and Return on Assets (ROA). The study focuses on PT Adhi Karya (Persero) Tbk, utilizing secondary data derived from the company's annual financial reports spanning 2014 to 2023. An associative quantitative approach was employed, with data collected through documentation. Data analysis involved descriptive statistics, classical assumption testing, multiple linear regression, correlation analysis, determination testing, and hypothesis testing, all performed using SPSS version 27. The findings indicate that, on a partial basis, the Debt to Equity Ratio does not significantly impact Return on Assets, as evidenced by a t-value of -1.001 (less than the critical t-value of 2.365) and a significance level of 0.350 (greater than 0.005). Conversely, Firm Size does have a significant partial effect on Return on Assets, with a t-value of -4.838 (less than 2.365) and a significance value of 0.002 (less than 0.005). Collectively, Leverage and Firm Size significantly affect Profitability, as reflected by an F-value of 14.492 (greater than the critical F-value of 4.74) and a significance level of 0.003 (less than 0.05). The Adjusted R-Square value indicates that 75% of the variation in Return on Assets can be explained by the variables studied, while the remaining 25% is attributed to factors beyond the scope of this research.